Political Behavior and the Emotional Citizen Participation and Reaction in Turkey - Erisen, Cengiz (Palgrave Studies in Political Psychology, 2018)
This book studies the role of emotions, such as anger, anxiety, and enthusiasm, across various domains of political behavior in Turkey. The author considers how emotions affect evaluations of leadership performance, levels of intolerance, likelihood of following and participating in politics, perceived threats from terrorism, and electoral decisions, including vote choice. Using a nationally representative survey and experimental data, this study empirically analyses the causal associations among the primary factors explaining the Turkish electorate's political attitudes and behaviours. The book will be of particular interest to academics, university students, and policymakers seeking to learn more about contemporary Turkish politics amid the recent political and social turmoil that has affected all parts of this society.